Violation regulation of financial services authority (FSA), financial performance, and corporate social responsibility disclosure - Habib Muhammad Shahib; Soni Agus Irwandi (Universitas Hayam Wuruk Perbanas, 2016)
So far, there has been a bureaucracy reform and implementation of new regulations for good governance capital markets. However, policy violations are still frequent. For example, cases of violation of financial regulations leading to fraudulent financial reporting occurred in several companies listed on the Indonesia Stock Exchange. This study aims to examine the empirical facts related to the legitimacy theory with-in the scope of violation of financial regulation, financial performance and social responsibility disclosure of non-financial companies in Indonesia Stock Exchange. The data were obtained from the Indonesia Stock Exchange. There were 24 non-financial violator-companies of financial regulation chosen as the sample. These data, in relation to the research hypotheses, were analyzed by using a path analysis test. The result showed there were no significant effect of the violations of financial regulations on financial performance and the level of corporate social responsibility disclosure. Therefore, this study confirms legitimacy theory in different forms.